Electrophysiological indices of visual food cue-reactivity. Differences in obese, overweight and normal weight women. (1st February 2015) - Hume, David John; Howells, Fleur Margaret; Rauch, H.G. Laurie; Kroff, Jacolene; Lambert, Estelle Victoria
Highlights: Food cues amplified right frontal and left central beta power in overweight women. Neutral cues induced blunted left and right pre-frontal theta power in obese women. Food cues elicited greater right parietal ERP P200 amplitude in overweight women. Food cues elicited shorter right parietal ERP P300 latency in obese women. Food cue-reactivity correlated with eating behaviour, body image and % fat mass. Abstract: Heightened food cue-reactivity in overweight and obese individuals has been related to aberrant functioning of neural circuitry implicated in motivational behaviours and reward-seeking. Here we explore the neurophysiology of visual food cue-reactivity in overweight and obese women, as compared with normal weight women, by assessing differences in cortical arousal and attentional processing elicited by food and neutral image inserts in a Stroop task with record of EEG spectral band power and ERP responses. Results show excess right frontal (F8 ) and left central (C3 ) relative beta band activity in overweight women during food task performance (indicative of pronounced early visual cue-reactivity) and blunted prefrontal (Fp1 and Fp2 ) theta band activity in obese women during office task performance (suggestive of executive dysfunction). Moreover, as compared to normal weight women, food images elicited greater right parietal (P4 ) ERP P200 amplitude in overweight women (denoting pronounced early attentional processing) and shorter right parietal (P4 ) ERP P300 latency in obese women (signifying enhanced and efficient maintained attentional processing). Differential measures of cortical arousal and attentional processing showed significant correlations with self-reported eating behaviour and body shape dissatisfaction, as well as with objectively assessed percent fat mass. The findings of the present study suggest that heightened food cue-reactivity can be neurophysiologically measured, that different neural circuits are implicated in the pathogenesis of overweight and obesity, and that EEG techniques may serve useful in the identification of endophenotypic markers associated with an increased risk of externally mediated food consumption.